Avaliação da toxicidade do óleorresina da espécie Copaifera Reticulata - SILVA, Lauren Yasmin Duarte da (Universidade Federal do Oeste do Pará, 2024)
Plants produce a wide range of chemical substances that can trigger a variety of diverse biological activities, and as far as they are concerned, represent an important therapeutic resource for a large part of the population, especially those who do not have direct access to medicines. Therefore, the incorrect use of medicinal plants can trigger a negative response to people's health. The relationship between the intensity of exposure, concentration and duration of exposure tends to directly influence the level of intoxication, therefore, it is essential to know the level of toxicity of medicinal plants and natural products in general. This is a study with the aim of carrying out pre-clinical in vivo safety tests to evaluate acute oral, acute dermal and dermal toxicity in repeated doses of Copaifera reticulata oil resin in Wistar rats. The plant material, Copaifera reticulata oil resin, was obtained from the Tapajós National Forest - FLONA, in the municipality of Belterra, in the Western Region of Pará. For the identification of chemical compounds, chromatographic analyzes were carried out with a mass detector (GC-MS), equipped with an autosampler (TriPlus RSH) and apolar capillary column (Tr-5; 30 m x 0.25 mm ID x 0.25 μm). Toxicity studies were carried out in accordance with protocols OECD-423/2001 (acute oral - single dose of 2000 mg/kg of animal body weight), OECD - 402/2017 (acute dermal dose - 2000 mg/kg body weight of the animal,) and OECD – 410/1981 (dermal in repeated doses - doses of 1000mg, 250mg, 62.5mg mg/kg of animal mass), carried out at the vivarium of the University of the State of Pará, campus Santarém. As for the chemical characterization of the compounds identified in Copaíba (Copaifera reticulata), 68.26% correspond to sesquiterpenes and 24.89% to diterpenes. For oral and acute dermal toxicity studies, no significant changes were observed in clinical signs and other systems. Only some animals treated with Copaiba at a dosage of 1,000 mg/kg, in dermal toxicity in repeated doses, showed changes such as increased dermal sensitivity, agitation, restlessness, pilo erection and some cases of diarrhea. In this same toxicity and dosage, in the hematological parameters, alterations in the number of leukocytes were observed, only in male animals, however such alterations are statistically insignificant. Through the results achieved and in the midst of the experimental conditions employed and their analysis correlated with the scientific literature, it was possible to conclude that the oil resin from Copaifera reticulata presents a relative margin of safety for the suggestive use as a therapeutic agent, considering that the experiment with the oil resin , did not cause toxicological clinical signs, with no death records, in addition to the non-existence of significant changes in the parameters evaluated in the animals used in the research. Therefore, it is necessary to develop new studies with different species of Copaifera oil resin.